Financial culture and indebtedness of the clients of the savings and credit cooperatives - Díaz Tantalean, Neiser Abel (2022)
The purpose of the study is to determine the relationship between the financial culture and the indebtedness of the clients of the savings and credit cooperatives of Jaén by 2022. The methodology used is a quantitative approach of descriptive correlational level with a non-experimental design, the sample is made up of by 334 participants, the technique to collect the data is the survey and the instrument the questionnaire, the results show that 38% of the respondents think that the financial culture of the partners is regular and 41% of the partners specify that the level of indebtedness is regular, likewise a Spearman's rho coefficient of -0.549 and a p. value of "0.000" less than (0.05). It is concluded that there is a highly significant inverse relationship between the financial culture and the level of indebtedness of the clients of the savings and credit cooperatives of Jaén. Also, the factors of the financial culture are inversely related to the level of indebtedness of the members of the savings and credit cooperative of Jaén to 2022.